Pemaknaan Khalayak Mengenai Brand Message Choco Drink (Studi Resepsi Konten Akun Instagram @Chocodrink.id) - Artyasto Jatisidi; Kevin Sebastian (Avant Garde, 2022)
Massive content on social media today makes it a new challenge for brands to be able to survive in digital marketing on social media, brands must be able to create content that is relevant to the audience. This study aims to find out how the meaning of Chocodrink's target audience regarding brand messages and Chocodrink's digital marketing techniques in the content of the @Chocodrink.id instagram account. This research method is qualitative with Stuart Hall's Reception Analysis Theory which positions three audiences in three positions, namely dominant, negotiating and opposition. The subject of this study is the Chocodrink audience with the object of research, namely the Chocodrink brand message in the content of the @Chocodrink.id instagram account. Data collection was obtained through in-depth interviews with five informants who were selected by purposive sampling. The conclusion of the research is that the informants accept the meaning conveyed in the content of the @Chocodrink.id instagram account, the audience's meaning such as with the Chocodrink brand message and digital marketing techniques conveyed by Chocodrink. So that the informants can easily interpret the message that Chocodrink wants to convey. In this case it can be said that the content presented by the brand is in accordance with the characteristics of the audience and the message conveyed can be well received by the audience.